Chaotic self-adaptive interior search algorithm to solve combined economic emission dispatch problems with security constraints - Rajagopalan A.; Kasinathan P.; Nagarajan K.; Ramachandaramurthy V.K.; Sengoden V.; Alavandar S. (John Wiley and Sons Ltd, 2023)
Genetic algorithms; Learning algorithms; Multiobjective optimization; Particle swarm optimization (PSO); Combined economic emission dispatch; Multi-objective optimization problem; Performance metrics; Search Algorithms; Security constraint; Electric load dispatching